Improving Students’ Vocabulary Mastery through Reading Racetracks - Kurniawan, Asep; Nurindah, Nurindah; Siam, Siam (Universitas Halu Oleo, 2021)
The objective of this study is to find out the significant effect of using Reading Racetracks on students‟ vocabulary mastery at SMPN 1 Konawe Selatan. Reading Racetracks as technique in learning teaching process. This research used quasi experimental design, the population was eighth grade students, and the sample was class VIII/A as the experimental group and VIII/D as control group. The experimental group consisted of 24 students and control group consisted of 20 students. The research instrument consisted of 30 multiple choices and 5 cloze test of vocabulary test. To collect the data, pre-test was given and taught by using Reading Racetracks technique, and giving post-test. Mean of post-test (77.58) in experimental class was higher than pre-test score (53.33). While, in control class was also had improvement but not too significant. It could be seen on post-test score (67.65) was higher than pre-test score (40.30).Based on the calculation of T-test, it showed that tcount = 2.199, while t-table = 2.010 at level of α = 0.05 with DF = 42. It means that tcount was higher than ttable, Therefore, H0 was rejected and H1 was accepted. This could be concluded that there was a significant effect of using Reading Racetracks to improve students‟ vocabulary mastery at Class VIII/A of SMPN 1 Konawe Selatan.